PENINGKATAN PENERAPAN INTERVENSI GIZI TERINTEGRASI UNTUK ANAK STUNTING DI KABUPATEN PASAMAN BARAT - Denas Symond; Idral Purnakarya; Hafifatul Auliya Rahmy; Firdaus Firdaus; Erwinda Erwinda (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2020)
Stunting is a complex development problem, and it’s related to most goals of SDGs, ranging from eradicating poverty, eliminating hunger, malnutrition (including stunting), improving maternal and child health, eradicating disease, improving the environment and sanitation, food security, nutrition, gender equality and cooperation between nations. West Pasaman is one of the locus districts in West Sumatra Province. So the role of universities in assisting prevention and stunting prevention programs is crucial. This assistance activity aims to implement integrated nutrition interventions for stunting prevention and countermeasure in West Pasaman district. The method of activities undertaken is coordination and consolidation with the application of the IGT-AS (Integrated Nutrition-Child Stunting Intervention) concept from the college level, district, sub-district, and village levels. While the survey method by collecting nutritional status data at the family level. The assistance provided by tertiary institutions resulted in proposed interventions to OPD (Regional Apparatus Organizations) related to nutrition interventions at the Nagari / Village level by implementing five intervention pillars through Nagari / Village institutions and the support of OPD District which has an extension at the District and Village / Nagari levels. The survey results obtained the nutritional status of Height for age in Nagari Kajai West Pasaman found 128 children were Stunting (32.8%), children under five with exclusive breastfeeding by 60.5%, Integrated Healthcare Center sits in the last three months were found to be the most weighted regularly at 67.7%, and mothers of children under five who attend Toddler Family Development (BKB) in Nagari Kajai are still low at 14.9%. The role of universities is crucial, especially in increasing the capacity of OPD in determining intervention programs, expanding the capacity of health workers, cadres of Integrated Healthcare Center activities, and community empowerment.